2014
DOI: 10.1159/000368914
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for Discontinuation of Lipid-Lowering Medications in Patients with Chronic Kidney Disease

Abstract: Background/Aims: Many patients with chronic kidney disease (CKD) do not receive lipid-lowering therapy despite their high cardiovascular risk. The reasons for this are unknown. Methods: We have conducted a retrospective cohort study of discontinuation of lipid-lowering drugs in patients with CKD stage 3 and higher treated in practices affiliated with two academic medical centers between 2000 and 2010. Information on medication discontinuation and its reasons was obtained from electronic medical records, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…The data sources for the studies were varied, with most utilizing information from EHRs or other clinical databases. Within these studies, the majority only included structured data in their models (47, 48, 49, 50, 58, 59, 60, 61, 62) while a few incorporated both structured and unstructured data from these resources (45, 43, 44, 63). Another source of data was surveys, questionnaires, or interviews, where again the majority of studies used only structured data in their models (46, 53, 54, 51, 57), with only one study applying NLP methods and used both structured and unstructured data (64).…”
Section: Resultsmentioning
confidence: 99%
“…The data sources for the studies were varied, with most utilizing information from EHRs or other clinical databases. Within these studies, the majority only included structured data in their models (47, 48, 49, 50, 58, 59, 60, 61, 62) while a few incorporated both structured and unstructured data from these resources (45, 43, 44, 63). Another source of data was surveys, questionnaires, or interviews, where again the majority of studies used only structured data in their models (46, 53, 54, 51, 57), with only one study applying NLP methods and used both structured and unstructured data (64).…”
Section: Resultsmentioning
confidence: 99%
“…We also found that CKD patients had a high rate of statin discontinuation. According to Morrison and colleagues, the most common reason for long-term discontinuation of lipid-lowering medications in CKD patients is adverse reactions [ 24 ]. However, due to the retrospective nature of our study design, it was not possible to explore the potential reasons behind statin discontinuation in the current research.…”
Section: Discussionmentioning
confidence: 99%
“…On the sentence level, only $2% of the sentences from 1867 notes contain DDCs. Therefore, although DDC events are common in patient care, 4,17,18 they are sparsely documented in clinical narratives, making NLP-based DDC detection a challenge.…”
Section: Data Annotation Schema Annotationmentioning
confidence: 99%
“…Existing studies typically group DDC reasons into 4 categories: 1) adverse events (AEs), 2) lack of treatment effectiveness, 3) patient preference/nonadherence, and 4) medication being no longer necessary. 4,5 The various categories contribute differently. Studies on causes of anti-tumor necrosis factor discontinuation, for instance, showed that AEs were responsible for treatment discontinuations in 48.7% of cases, and lack of treatment effectiveness represented the most significant single cause for anti-tumor necrosis factor treatment discontinuation (50%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation